농업교육 참여에 따른 농가소득 증가율 추정 - 강혜정 (한국농촌경제연구원, 2011)
This study is designed to estimate how much farm income increases after participating agricultural educations. The data used consist of 433 farms that had received agricultural educations during the past three years. Double-bounded dichotomous choice method is applied to ask the growth rate of farm income after participating agricultural educations. This survey method is attempted to reduce its inaccuracy caused by an open question asking farm income directly. The empirical evidence suggests that the income growth rate by agricultural educations is 17.54% on average. Especially, the results show that the average growth rate of high income is higher than that of low income farms.
Keywords: 농업교육; 농가소득증가율; 이중양분선택형질문법; agricultural education; farm income growth; double-bounded dichotomous choice method